Cropping system yield gaps can be narrowed with more optimal rotations in dryland subtropical Australia. (September 2020) - Hochman, Zvi; Horan, Heidi; Navarro Garcia, Javier; Hopwood, Garry; Whish, Jeremy; Bell, Lindsay; Zhang, Xiying; Jing, Haichun
Abstract: Closing the gap between yields currently achieved on farms and those that can potentially be achieved with best practice and current technology (the yield gap) is a key strategy to intensify grain production without expanding cropland. Much research has been done to quantify the yield gap of wheat, maize and rice globally and of wheat, barley, canola, sorghum and pulse crops in Australia. However, crops are grown in rotations (recurring crop sequences) that vary in their cropping intensities and in the diversity of their species. Little is known about yield gaps at the cropping system level, especially in regions where there are many possible combinations of crop types and fallow periods. This prompted us to investigate crop rotations in Australia's subtropical grains region where current crop rotations include winter and summer cropping with cereal, pulse and oilseed crops interspersed with fallow periods ranging from nil to 18 months duration. To determine the system level yield gaps, we simulated the water-limited yield potential of 26 locally practiced crop rotations for over 800 weather stations by up to 3 soil types per station. We captured the impact of climate variability with 30–35 years by 2–7 fields per rotation for each site. We expressed the results in terms of energy, protein and revenue per hectare per year and mapped the results of the optimal rotations over the cropping zone. Surprisingly, a single rotation (sorghum/fallow/mungbean/wheat/fallow/chickpea rotation; with 4 crops in 3 years, balanced between summer and winter crops and between cereal and pulse crops) was optimal for revenue over almost the whole subtropical grain zone. Using revenue as the metric for yield gaps at statistical local area scale we found, over the whole subtropical zone, a mean revenue gap of 970 /ha/yr. This represents a relative revenue (Revenue% = 100 x (actual revenue/water-limited revenue)) of 34% which is much lower than expected from the 40–60% relative yields achieved by individual crops. We investigated whether growers may select rotations that have lower revenue than the optimal rotation in response to economic factors such as profit and risk. We found that for much of the area the same rotation that optimised revenue also optimised profit. However, for some of the cropping zone, particularly in the south western portion, a different, less intensive and more winter dominant, rotation was most profitable. Similarly, risk averse farmers may choose less productive and profitable rotations with less risk. Highlights: This research has produced the first regional-scale maps of cropping systems yield gaps. Productivity of cropping in Australia's subtropical grain zone is only 34% of its potential. Profit-risk trade-offs may be responsible for growers choosing less productive rotations. These maps and trade-off charts may be useful to engage stakeholders about cropping system design.